Activity of the main dose-generating radionuclides in water bodies of the belarusian sector of the Сhernobyl NPP zone and their dose loads for the biota - Zhuravkov, Vladislav; Golubev, Alexander; Yukhnevich, Victoria; Bodilovskaya, Olga (Journal of the Belarusian State University. Ecology, 2023)
In 2014–2015 we determined the activity of the most abundant radionuclides 90Sr, 137Cs and 241Am in the water column, bottom sediments and dominant species of macrophytes and mollusks in two water bodies of the Belarusian sector of the near zone of the Chernobyl nuclear power plant (ChNPP). Of these, the low-flowing Perstok Lake is the most contaminated with radionuclides water body in Belarus sector of ChNPP, and the flowing Borshchevska waterlogging, which has formed in the past two decades, is characterized by an average level of radiation contamination for the near zone of ChNPP. These data were used to calculate the values of the absorbed dose rate (ADR) during internal exposure for the dominant biota of water bodies from the indicated complex of radionuclides. In the bottom sediments of the Perstok Lake, the activity of 90Sr and 137Cs reached 185 and 468 kBq∙m-2, respectively, and in the Borshchevska waterlogging, respectively 61 and 212 kBq∙m-2, which significantly exceeds the pre-accident level. Among the biota organisms, macrophytes were characterized by the highest levels of the activity of 90Sr and 137Cs. In the Perstok Lake the values of 90Sr and 137Cs activities for them reached 24700 and 40100 Bq∙kg-1 dry weight, respectively, and in the Borshchevska waterlogging – 8747 and 3780 Bq∙kg-1 dry weight. Among the mollusks of the Perstok Lake Anodonta spp. shells were characterized by the highest activities of 90Sr and 137Cs – up to 50216 and 1049 Bq∙kg-1 of wet weight. The activity of 137Cs in the soft tissues of mollusks is much lower – no more than 780 Bq∙kg-1 of live weight. The activity of 241Am in bottom sediments and macrophytes of the Perstok Lake during the study period was significantly lower – no more than 4.4 kBq∙m-2 and 202 Bq∙kg-1 of dry weight, and in the Borshchevska waterlogging – 2.6 kBq∙m-2 and 48.1 Bq∙kg-1 dry weight. 241Am activity in soft tissues and shells of mollusks from both reservoirs was not recorded in most cases. The total values of ADR from all the studied radionuclides in macrophytes and mollusks varied within 10–28 mkGy∙day-1, and in the mollusk of Lymnaea stagnalis – 64 mkGy∙day-1. The greatest contribution to the formation of the total ADR in macrophytes (within 42–99 %) and mollusks (up to 99 %) is made by the 90Sr + 90Y isobar. In most cases, the contributions of the 137Cs+137Ba and 241Am isobar to the total ADR values are extremely insignificant. Only for the roots of Typha angustifolia their contribution reached 37.7 and 20.3 %, respectively. Currently, in the near zone of ChNPP, against the background of a decrease in the activity of 90Sr and 137Cs, an increase in the activity of 241Am is observed. It is predicted that by the middle of the XXI century 241Am will become the main dose-forming radionuclide for the biota of water bodies in the near zone of the ChNPP.